Comparison of micro-CT post-processing methods for evaluating the trabecular bone volume fraction in a rat ACL-transection model. Issue 14 (3rd October 2016) - Chin, K.E.; Karamchedu, N.P.; Patel, T.K.; Badger, G.J.; Akelman, M.R.; Moore, D.C.; Proffen, B.L.; Murray, M.M.; Fleming, B.C.
Abstract: Trabecular bone volume fraction assessments are likely sensitive to the analysis method and selection of the region of interest. Currently, there are several methods for selecting the region of interest to analyze trabecular bone in animal models of post-traumatic osteoarthritis. The objective of this study was to compare three published methods for determining the trabecular bone volume fraction of the medial tibial epiphyses in ACL transected and contralateral ACL intact knees. Micro-computed tomography images of both knees were obtained five weeks post-operatively and evaluated using three methods: (1) the Whole Compartment Method that captured the entire medial compartment, (2) the centrally located Single Core Method, and (3) the Triplet Core Method that averaged focal locations in the anterior, central, and posterior regions. The Whole Compartment Method detected significant bone loss in the ACL transected knee compared to the ACL intact knee ( p <0.001), with a loss of 15.2±3.9%. The Single Core and the Triplet Core Methods detected losses of 7.5±10.5% ( p =0.061) and 14.1±13.7%( p =0.01), respectively. Details regarding segmentation methods are important for facilitating comparisons between studies, and for selecting methods to document trabecular bone changes and treatment outcomes. Based on these findings, the Whole Compartment Method is recommended, as it was least variable and more sensitive for detecting differences in the bone volume fraction in the medial compartment.